2019
DOI: 10.1371/journal.pone.0218664
|View full text |Cite|
|
Sign up to set email alerts
|

Social success of perfumes

Abstract: We study data on perfumes and their odour descriptors—notes—to understand how note compositions, called accords, influence successful fragrance formulas. We obtain accords which tend to be present in perfumes that receive significantly more customer ratings. Our findings show that the most popular notes and the most over-represented accords are different to those that have the strongest effect to the perfume ratings. We also used network centrality to understand which notes have the highest potential to enhanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In captive forest musk deer populations, we observed that, during the period when musk is formed in the males’ musk sac, it can be divided into different categories. Musk has previously been added to perfumes and cosmetics as an advanced fauna natural perfume [ 35 37 ]. However, abnormal musk has a bad smell that might make people feel uncomfortable and is, therefore, not qualified to be used as a perfume material ( Fig 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In captive forest musk deer populations, we observed that, during the period when musk is formed in the males’ musk sac, it can be divided into different categories. Musk has previously been added to perfumes and cosmetics as an advanced fauna natural perfume [ 35 37 ]. However, abnormal musk has a bad smell that might make people feel uncomfortable and is, therefore, not qualified to be used as a perfume material ( Fig 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypergraphs and their null models might be used to analyse other data sets. Among them are association-based data (e.g., ingredient-product networks [47,48], authorship networks [49], company-directorate networks [50]) or social networks in which higher-order interactions have been shown to be prominent [51,52]. The tools in this manuscript could be used to investigate such data as hypergraphs and so reveal organisational principles beyond their pairwise interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Hypergraphs and their null models might be used to analyse other data sets. Among them are association-based data (e.g., ingredient-product networks [47,48], authorship networks [49], company-directorate networks [50]) or social networks in which higher-order interactions have been shown to be prominent [51,52]. The tools in this manuscript could be used to investigate such data as hypergraphs and so reveal organisational principles beyond their pairwise interactions.…”
Section: Discussionmentioning
confidence: 99%